Samarium ion exchanged montmorillonite for high temperature cumene cracking reaction - Binitha, N. N.; Silija, P. P.; Suraj, V.; Z., Yaakob; Sugunan, S. (IOP Publishing Ltd, 2011)
Link to publisher's homepage at http://iopscience.iop.org/